2023
DOI: 10.1101/2023.04.25.538222
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Competition between transcription and loop extrusion modulates promoter and enhancer dynamics

Abstract: The spatiotemporal configuration of genes with distal regulatory elements, and the impact of chromatin mobility on transcription, remain unclear. Loop extrusion is an attractive model for bringing genetic elements together, but how this functionally interacts with transcription is also largely unknown. We combine live tracking of genomic loci and nascent transcripts with molecular dynamics simulations to assess the 4D arrangement of the Sox2 gene and its enhancer, in response to a battery of perturbations. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 94 publications
2
6
0
Order By: Relevance
“…The simulations presented here suggest that the sigmoidal relationship could emerge from productive interactions being limited to long events (> 1min) within a larger capture radius (∼400 nm) than that of Hi-C. In support of this idea, the time- and distance-gated model proposed here recapitulates several observations: the increased dependence of loop extrusion for transcription activation from long distances (27,32); the stronger effect of loop extrusion perturbations on the frequency of activation intervals compared to their duration (23); the fact that Sox2 transcription exhibits little temporal correlation with distance to its SCR enhancer - since the SCR lies within <400 nm of the promoter the vast majority of the time, the model predicts near uninterrupted enhancer-promoter communication (33,34); the strong temporal correlation between enhancer-promoter distance and transcription activity for artificial systems where the enhancer regularly explores distances outside of the ∼400 nm capture radius from the promoter (35,36). While other mechanisms have also been proposed to account for the non-linearity observed between chromatin contact matrices and transcription regulation (17,37,38), the simulations presented here demonstrate that the choice of a specific contact observable as a metric is not a neutral decision, but in itself can introduce non-linearities.…”
Section: Discussionsupporting
confidence: 73%
“…The simulations presented here suggest that the sigmoidal relationship could emerge from productive interactions being limited to long events (> 1min) within a larger capture radius (∼400 nm) than that of Hi-C. In support of this idea, the time- and distance-gated model proposed here recapitulates several observations: the increased dependence of loop extrusion for transcription activation from long distances (27,32); the stronger effect of loop extrusion perturbations on the frequency of activation intervals compared to their duration (23); the fact that Sox2 transcription exhibits little temporal correlation with distance to its SCR enhancer - since the SCR lies within <400 nm of the promoter the vast majority of the time, the model predicts near uninterrupted enhancer-promoter communication (33,34); the strong temporal correlation between enhancer-promoter distance and transcription activity for artificial systems where the enhancer regularly explores distances outside of the ∼400 nm capture radius from the promoter (35,36). While other mechanisms have also been proposed to account for the non-linearity observed between chromatin contact matrices and transcription regulation (17,37,38), the simulations presented here demonstrate that the choice of a specific contact observable as a metric is not a neutral decision, but in itself can introduce non-linearities.…”
Section: Discussionsupporting
confidence: 73%
“…It has been reported that the ParB/ParS system has minimal transcription disruption ( 21 , 28 ). Here we compared the effect of 8XLacO, 8XParSc or U2OS-8XNBS integration (P1 locus) on the transcription repression of the PPP1R2 gene ( Supplementary Figure S7A ).…”
Section: Resultsmentioning
confidence: 99%
“…Although there are four to ten nucleotide differences between Bc ParS1 or Bc ParS2 and the other ParSs, Bc ParB2/ Bc ParS2 (ANCHOR2) formed many non-specific foci regardless of the presence or absence of ParS in mammalian cells, which is excluded us from being utilized in the multicolor DNA labeling system. Bc ParB1/ Bc ParS1 (ANCHOR1) was recently used in the mESCs ( 28 ), but its robustness of labeling needs to be further validated. ANCHOR3 has been used successfully in several cases ( 21 , 27 , 28 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations